1975
DOI: 10.1037/h0076212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of testosterone propionate administered neonatally on puberty and bisexual behavior in female hamsters.

Abstract: Female hamsters were treated with oil, 3-/ig., 30-/ig., or 300-yug. testosterone propionate (TP) as neonates. Neonatal TP treatment delayed the onset of puberty by 4.5 days to an age near that previously reported for the male hamster. In addition, neonatal TP altered genital morphology, induced the capacity for mounting behavior, and at the highest dosage, disrupted the ability to bear and rear young. Vaginal and behavioral estrous cycles, however, were not influenced by neonatal TP. In a second experiment, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The present data are generally consistent with the demonstration that in the hamster, masculinization is more easily produced by neonatal hormone treatment than is defeminization and that defeminization consists of several independent component responses, each differentially sensitive to hormone dosage (DeBold & Whalen, 1975;Whitsett & Vandenbergh, 1975). Masculinization, as measured by induction of the ability to display mounting behavior, was produced readily by neonatal treatment with £2-17/3.…”
Section: Masculinization and Defeminization Referencessupporting
confidence: 89%
See 2 more Smart Citations
“…The present data are generally consistent with the demonstration that in the hamster, masculinization is more easily produced by neonatal hormone treatment than is defeminization and that defeminization consists of several independent component responses, each differentially sensitive to hormone dosage (DeBold & Whalen, 1975;Whitsett & Vandenbergh, 1975). Masculinization, as measured by induction of the ability to display mounting behavior, was produced readily by neonatal treatment with £2-17/3.…”
Section: Masculinization and Defeminization Referencessupporting
confidence: 89%
“…Each female was paired with a proven stud male for 3 min per day or until the female exhibited lordosis or fighting occurred. Details of the procedures for vaginal examination and behavioral testing are provided in Whitsett and Vandenbergh (1975).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies support the existence of such a sex difference in the hamster (Diamond, Mast, & Yanagimachi, 1974;Vandenbergh, 1971b). Whitsett and Vandenbergh (1975) produced evidence that this difference is regulated by hormonal conditions earlier in life. The administration of testosterone propionate to neonatal female hamsters delayed the onset of estrous cyclicity by several days to an age similar to that previously reported for the attainment of sexual maturity in males.…”
Section: Early Onset Of Androgen Secretionmentioning
confidence: 99%
“…It is unclear why mounting behavior was not facilitated by neonatal subcutaneous injections of TP in this study, since other investigators [40,41] found significant increases in mounting with similar doses of TP given to newborn fe male hamsters. This discrepancy could possibly be due to the fact that in both of the other studies the steroid was ad ministered within the first 48 postnatal hours, whereas in this experiment the hamsters were more than 48 h old when given the TP injections.…”
Section: Male Sexual Behaviormentioning
confidence: 61%